Consultation (Shura): Formation, Ruling, Procedures, and the Binding Nature of its Resolutions (Salam International Academic Journal, 2024)
This research article addresses a critical and significant issue: the concept of Shura (consultation) and the principle of Shuraism. In Islamic jurisprudence, Shura serves as a fundamental pillar of societal life, gaining even greater significance in matters that pertain to the majority of the community, particularly those of a political nature. Shura is recognized as a religious obligation, with a consensus made among Islamic scholars affirming its importance. Islam has delineated broad domains for consultation and established specific criteria for those who are eligible to participate as member of Shura. Regarding the implementation of Shura, Islamic guidelines mandate that deliberations on social issues must be conducted collectively within a Shura council, as individual consultations are insufficient.In the contemporary context, characterized by the absence of Mujtahid rulers (qualified jurists) in the Islamic world, the decisions reached through Shura must be binding, as required by Islamic law. These decisions shall be based on the principle of majority rule, which is considered as a primary mechanism for decision-making within the Shura framework. By adhering to these Islamic precepts in the implementation of Shura under the current circumstances, numerous challenges confronting Muslim societies can be effectively addressed. This study explores these themes and related matters in detail.
Keywords: Shura; implementation of Shura; domains of Shura; binding nature of Shura decisions; majority rule